Analysis of Factors Hindering Arabic Language Teaching - Akhmad Zainudin; Lili Musyafa’ah (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the factors inhibiting Arabic language teaching at SMP IT An-Najiyah. The main issues identified include students limited communicative competence, linguistic difficulties, and the lack of Arabic language habituation outside the classroom. This research employs a qualitative case study approach through interviews, observations, and documentation involving teachers, students, and curriculum staff. Data were analyzed using the Miles and Huberman model with validity ensured through credibility, transferability, dependability, and confirmability. The findings indicate that the barriers to Arabic learning are multidimensional, encompassing linguistic, psychological, pedagogical, and managerial aspects. In conclusion, the effectiveness of Arabic language teaching requires a holistic approach that emphasizes linguistic habituation, institutional support, and pedagogical innovation to optimize students’ communicative abilities.